Population aging: a look from nursing practice based on the Nola J. Pender model - María de los Ángeles Villegas Dorticós; Zenia Tamara Sánchez García; Omayda Urbina Laza; Noel Alberto Pardillo Mustelier; Jacquelin Cordero Odery; Maydelis Gómez Valdivia (Medisur)
Population aging is not an exclusive phenomenon of modern society; it has been present in all social development stages and has always been of interest to philosophy, art and medicine. A bibliographical review is presented for evaluating the Nola J. Pender model application in health promotion, and its applicability from its theoretical vision in the community nursing practice in aging population. The theoretical aspects expressed by her, her main assumptions and her relationship with population aging are analyzed, in addition to exposing her theoretical contributions, the importance of her application for the family, the community and her contribution to the development of nursing not only in Cuba but in the world; if we start from the fact that Cuba is among the oldest countries in Latin America. Health promotion motivated by the desire to increase well-being and update human potential is currently considered a powerful tool that allows promoting attitudes, motivations and actions based on the concept of self-efficacy, the commitment of individuals to change of behaviors to promote health, not only about aging itself, but from aging. The main assumptions of Nola J. Pender in the health promotion model place it as a reference framework in research, by strengthening the profession and basing its work objectively on the interests of professionals and the people needs.